The Effect of Head-Up Display on Game Player’s Eye Movements: Systematic Literature Review - Arief Hartanto; Hafiz Aziz Ahmad; Etika Vidyarini (Journal of Applied Informatics and Computing, 2026)
Head-up display (HUD) is a part of the game interface that is important as a medium of information for players. HUD generally takes the form of numerical, textual, or symbolic indicators in games. Interaction between game players and the HUD produces measurable differences in eye-movement behaviour, operationalized here as fixation count, fixation duration, and saccade velocity/amplitude. While several systematic literature reviews (SLRs) have examined eye tracking in games, none has isolated the HUD as the primary explanatory variable or reconciled the conflicting expert-novice findings that recur across this literature. This article addresses that gap by mapping research trends on HUD-driven eye movement and by synthesizing the recurring methodological practices used to collect eye-tracking data in this domain, to inform, rather than certify, future protocol design. Guided by the PRISMA approach, records were drawn from Google Scholar, Scopus, and ScienceDirect; ten studies published between 2015 and 2025 met the inclusion criteria and were analyzed through qualitative narrative synthesis (no meta-analysis was performed, given cross-study heterogeneity in eye trackers, tasks, and outcome metrics). The synthesis shows that fixation- and saccade-based outcomes diverge between expert and novice players in direction as well as magnitude, and that this divergence tracks genre-specific task demands (e.g., FPS/RTS versus MOBA versus racing) rather than a single uniform pattern. These findings are offered as an evidence base for eye-tracking protocol design in game-HUD research, not as a validated standard.